Pengaruh Budaya Kerja dan Lingkungan Kerja terhadap Kinerja melalui Motivasi dan Komitmen Organisasi (Studi di Komisi Pemilihan Umum Kabupaten Karanganyar) - Sri Handoko Budi; Achmad Choerudin; Winarna Winarna (STIE AUB Surakarta, 2016)
Purpose of this research is to known effect of work culture and work environment to motivation and organizational commitment, and effect of each variables to performance of Komisi Pemilihan Umum employees of Karanganyar Regency. The technique sampling used in this study is census method. The sample in this research is 32 respondents. The data collecting techniques is used observation and questionnaires. The data analysis technique is used research instrument test such as validity and reliability tests; linearity test; hypothesis test such as path analysis, t test, F test, determination coefficient; variable correlation. The test results shown that all instruments are valid and reliable. The result of this research shown that: Work culture and work environment has positive significant effect both to motivation and organizational commitment. Work environment, motivation and organizational commitment has positive significant effect to performance, but work culture have negative insignificant effect to performance. Work culture and work environment has positive significant effect to performance both through motivation and organizational commitment. Work culture, work environment, motivation and organizational commitment simultaneously influenced performance. The results of path analysis shown that: Indirect effect of work culture to performance through motivation is more effective rather than its direct effect. Direct effect of work environment to performance is more effective rather than its indirect effect through motivation. Indirect effect of work culture to performance through organizational commitment is more effective rather than its direct effect. Indirect effect of work environment to performance through organizational commitment is more effective rather than its direct effect. Variabel intervening motivation in this research is able to mediated work culture to performance, but it unable to mediated work environment to performance. Variabel intervening organizational commitment in this research is able to mediated work culture and work environment to performance. Indirect effect of work culture to performance through organizational commitment is most of dominant path effect to performance. The total effect of work culture to performance through organizational commitment is most dominant total effect to performance.Keywords: Work culture, work environment, motivation, organizational commitment and performance.